Short Communication: Characteristic of Anodendron paniculatum (Apocynaceae) in Mount Nglanggeran, Yogyakarta, Indonesia - WIDODO WIDODO; MUHAMMAD JAâ€™FAR LUTHFI (Society for Indonesian Biodiversity, 2017)
Widodo, Luthfi MJ. 2017. Short Communication: Characteristic of Anodendron paniculatum (Apocynaceae) in Mount Nglanggeran, Yogyakarta, Indonesia. Biodiversitas 18: 645-651. Anodendron paniculatum was found in climbing route of Mount Nglanggeran, Yogyakarta at coordinates location of 7Â°50'29.6